Transient ciliochoroidal detachment after microhook ab interno trabeculotomy: Its frequency and potential risk factors - Miyako, Fumiya; Hirooka, Kazuyuki; Onoe, Hiromitsu; Okada, Naoki; Okumichi, Hideaki; Kiuchi, Yoshiaki (Frontiers in Medicine, 2022)
Purpose: To investigate ciliochoroidal detachment (CCD) frequency and risk factors after performing microhook ab interno trabeculotomy (μLOT). Methods: A retrospective evaluation of 62 eyes of 62 patients who underwent μLOT and were subsequently examined by anterior-segment optical coherence tomography (AS-OCT) found CCD at 1 day, and 1 and 2 months after surgery. Results: In the 62 patients (mean age 67.3 ± 13.9 years), AS-OCT detected CCD in 18 eyes (29%) at 1 day after surgery, which disappeared within 1 month. Comparisons between the CCD vs. the non-CCD group showed the mean IOPs were 11.7 ± 1.5 mmHg vs. 14.4 ± 1.0 mmHg at day 1 (P = 0.13), 12.2 ± 1.1 mmHg vs. 14.8 ± 0.7 mmHg at day 7 (P = 0.06), 12.2 ± 0.7 mmHg vs. 12.9 ± 0.5 mmHg at 1 month (P = 0.48), and 11.3 ± 0.7 mmHg vs. 12.7 ± 0.5 mmHg at 2 months (P = 0.09). For postoperative IOP, there were no significant differences observed. After undergoing μLOT, multiple regression analysis demonstrated that the CCD development might be influenced by the presence of a thinner central corneal thickness. Conclusions: Approximately one-third of all patients exhibited CCD after μLOT. A thinner central corneal thickness was found to be a risk factor for developing CCD.